Do otolaryngology residency applicants relocate for training?. (30th July 2015) - Gebhard, Grant M.; Hauser, Leah J.; Dally, Miranda J.; Weitzenkamp, David A.; Cabrera‐Muffly, Cristina
Abstract : Objectives/Hypothesis: To determine whether there is an association between the geographic location of an applicant's undergraduate school, medical school, and residency program among matched otolaryngology residency applicants. Study Design: Observational. Methods: Otolaryngology residency program applications to our institution from 2009 to 2013 were analyzed. The geographic location of each applicant's undergraduate education and medical education were collected. Online public records were queried to determine the residency program location of matched applicants. Applicants who did not match or who attended medical school outside the United States were excluded. Metro area, state, and region were determined according to US Census Bureau definitions. Results: From 2009 to 2013, 1, 089 (78%) of 1, 405 applicants who matched into otolaryngology residency applied to our institution. The number of subjects who attended medical school and residency in the same geographic region was 241 (22%) for metropolitan area, 305 (28%) for state, and 436 (40%) for region. There was no difference in geographic location retention by gender or couples match status of the subject. United States Medical Licensing Exam step 1 scores correlated with an increased likelihood of subjects staying within the same geographic region ( P = .03). Conclusions: Most otolaryngology applicants leave their previous geographic area to attend residency. Based on these data, the authors recommend against giving weight to geography as a factor when inviting applicants to interview. Level of Evidence: NA Laryngoscope, 126:829–833, 2016